Correlation between bone mineral density and vitamin d status among patients with type 2 diabetes mellitus in United Arab Emirates - Allam, Hilda (2025)
Patients with type 2 diabetes (T2DM) may have a normal or high bone mineral density (BMD) with compromised bone structure. Inadequate vitamin D levels may reduce BMD and contribute to the development of diabetes. However, the results remain still controversial, and the underlying mechanism influencing BMD in T2DM are not fully understood. Factors such as age, sex, ethnicity, glycemic control, and vitamin D levels contribute to these variations. This study aimed to evaluate the BMD T score and correlate it with serum levels of vitamin D [25(OH)D], inflammatory, and bone markers in Emirati patients with T2DM. A cross-sectional study took place at the outpatient diabetic clinics of University Hospital Sharjah and Al Qassimi Hospital. A total of 128 Emirati individuals with T2DM aged 25 to 65 years were recruited (male: 46, female: 82). Participants underwent anthropometric measurements, and blood samples were collected to assess diabetic markers, bone and inflammatory markers, parathyroid hormone (PTH), calcium and vitamin D levels. Additionally, genetic polymorphisms in vitamin D receptor (VDR) and osteocalcin genes were analyzed for association with BMD and vitamin D. BMD was assessed using quantitative ultrasound scan (QUS) at the cancellous bone. According to QUS measurements, 69.5% of participants had low BMD, while 30.5% had normal BMD. Vitamin D levels were found to be low in 44.5% of participants, whereas 55.5% had optimal levels. BMD was significantly correlated with vitamin D levels (r= 0.297, p < 0.001), whereas bone markers did not significantly differ between normal and abnormal BMD groups The genetic analysis of VDR and osteocalcin gene polymorphisms showed no significant association with BMD or vitamin D levels. Poorly glycemic control (HbA1c ≥6.5) was observed in 83.6% of participants, while 16.4% had good glycemic control. Optimal vitamin D levels were associated with lower HbA1c (p = 0.030). Multivariate regression analysis revealed that vitamin D (β= 0.012, p <0.001) and sex (β= 0.393, p =0.017) had a significant positive association with BMD, whereas age showed a negative association with BMD (β= -0.033, p < 0.001). Logistic regression analysis further indicated that high insulin levels were linked with a better BMD score (OR=0.961; 95%CI: 0.925-0.999, p = 0.042), while high IL-6 levels were associated with low BMD scores (OR=1.289; 95%CI: 1.071-1.551, p = 0.007), suggesting that IL-6 is a strong predictor of BMD. In conclusion, BMD in T2DM is influenced by multiple factors, including vitamin D levels, age, sex, and inflammation. Given the high prevalence of low BMD, healthcare providers should monitor individuals at risk for fractures and consider intervention to improve health in patients with T2DM.